Quality of life and its association with predictors in lung transplant recipients: a latent profile analysis - Song, Liqin; Luo, Qing; Liu, Chunqin; Zhou, Ying; Huang, Danxia; Ju, Chunrong; Chen, Huifang; Wong, Thomas Kwok Shing; Chen, Jiani; Tan, Wenying; Miao, Chuyuan; Ma, Yu; et al. (Frontiers in Public Health, 2024)
Backgrounds Improving quality of life (QOL) is one of the main aims of lung transplantation (LTx). There is a need to identify those who have poor quality of life early. However, research addressing inter individual quality of life variability among them is lacking. This study aims to identify group patterns in quality of life among lung transplant recipients and examine the predictors associated with quality of life subgroups. Methods In total, 173 lung transplant recipients were recruited from one hospital in Guangdong Province between September 2022 and August 2023. They were assessed using the Lung Transplant Quality of Life scale (LT-QOL), Mindful Attention Awareness Scale (MAAS), Life Orientation Test-Revised scale (LOT-R), and Positive and Negative Affect Scale (PANAS). Latent profile analysis was used to identify QOL subtypes, and logistic regression analysis was used to examine the associations between latent profiles and sociodemographic and psychosocial characteristics. Results Two distinct QOL profiles were identified: “low HRQOL” profile [N = 53 (30.94%)] and “high HRQOL” profile [N = 120 (69.06%)]. Single lung transplant recipients, and patients who reported post-transplant infection, high levels of negative emotion or low levels of mindfulness and optimism were significantly correlated with the low QOL subgroup. Conclusion Using the domains of the LT-QOL scale, two profiles were identified among the lung transplant recipients. Our findings highlighted that targeted intervention should be developed based on the characteristics of each latent class, and timely attention must be paid to patients who have undergone single lung transplantation, have had a hospital readmission due to infection, exhibit low levels of optimism, low levels of mindfulness or high negative emotions.